Prevalence and predictors of food insecurity in conflict zones among displaced families in Lebanon during the war: a cross-sectional study - Hage Boutros, Paula; Hachem, Samah; Bou Serhal, Rola; Yazbeck, Noura; Azzam, Firas; Atallah, Bachir (Frontiers in Public Health, 2025)
BackgroundThe September–December 2024 conflict in Lebanon resulted in the displacement of over 1.5 million individuals, compounding the country’s existing economic and humanitarian crises. This study is aimed at assessing the prevalence and predictors of food insecurity (FI) among displaced families, focusing on key socioeconomic and psychological determinants.MethodsA cross-sectional survey was conducted among 400 displaced households across Lebanon. Data were collected on demographics, food security (Arab Family Food Security Scale), malnutrition (MUAC), income, education, household size, and mental health indicators including depression (PHQ-2), anxiety (GAD-2), PTSD (PCL-5), and resilience (BRS). Logistic regression identified predictors of FI.ResultsFI affected 42.4% of households, with 16.1% experiencing very low food security and only 28% fully food secure. Male participants reported higher food security than females (67% vs. 54.5%, p = 0.028). Larger families and monthly income < 700 (83.3% of sample) were significantly associated with FI (p = 0.003 and p < 0.001, respectively). Malnutrition prevalence was 7.2%, while obesity was 21%, reflecting a dual burden. Mental health distress was significantly higher among the food insecure: depression (3.91 vs. 2.56), anxiety (4.03 vs. 2.51), and PTSD (48.7 vs. 34.6); all p < 0.001. Resilience scores showed no association with FI (p = 0.106). Logistic regression identified low income (OR = 0.224), depression (OR = 2.099), anxiety (OR = 1.864), PTSD (OR = 1.023), and food aid (OR = 1.732) as significant FI predictors.ConclusionDisplaced Lebanese families face high rates of food insecurity linked to economic vulnerability and mental distress. While aid reduces malnutrition, it falls short in addressing FI. Integrated policies targeting income, mental health, and systemic aid delivery are essential for improving resilience and nutritional outcomes in crisis settings.